A New Method of Combination of Electroosmosis, Vacuum and Surcharge Preloading for Soft Ground Improvement - 刘汉龙 崔允亮 沈扬 丁选明 (China ocean engineering, 2014)
As a rapid and effective ground improvement method is urgently required for the booming land reclamation in China＇s coastal area, this study proposes a new combined method of electroosmosis, vacuum preloading and surcharge preloading. A new type of electrical prefabricated vertical drain （ePVD） and a new electroosmotic drainage system are suggested to allow the application of the new method. This combined method is then field-tested and compared with the conventional vacuum combined with surcharge preloading method. The monitoring and foundation test results show that the new method induces a settlement 20% larger than that of the conventional vacuum combined with surcharge preloading method in the same treatment period, and saves approximately half of the treatment time compared with the vacuum combined with surcharge preloading method according to the finite element prediction of the settlement. The proposed method also increases the vane shear strength of the soil significantly. The bearing capacity of the ground improved by use of the new proposed method raises 118%. In comparison, there is only a 75% rise when using the vacuum combined with surcharge preloading method during the same reinforcement period. All results indicate that the proposed combined method is effective and suitable for reinforcing the soft clay ground. Besides, the voltage applied between the anode and cathode increases exponentially versus treatment time when the output current of power supplies is kept constant. Most of the voltage potential in electroosmosis is lost at electrodes, leaving smaller than 50% of the voltage to be effectively transmitted into the soil.